2016
DOI: 10.1016/j.talanta.2015.12.081
|View full text |Cite
|
Sign up to set email alerts
|

Sample preparation for an optimized extraction of localized metabolites in lichens: Application to Pseudevernia furfuracea

Abstract: Lichens are symbiotic organisms known for producing unique secondary metabolites with attractive cosmetic and pharmacological properties. In this paper, we investigated three standard methods of preparation of Pseudevernia furfuracea (blender grinding, ball milling, pestle and mortar). The materials obtained were characterized by electronic microscopy, nitrogen adsorption and compared from the point of view of extraction. Their microscopic structure is related to extraction efficiency. In addition, it is shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…The BET specific surface area was found as 0.76 m 2 g −1 . Komaty et al (2016) have reported that the BET specific surface area of milled (mortar) Pseudevernia furfuracea was 1.8 m 2 g −1 . Pore size and its distributions are given in Fig.…”
Section: Characterization Of the Biosorbentmentioning
confidence: 99%
“…The BET specific surface area was found as 0.76 m 2 g −1 . Komaty et al (2016) have reported that the BET specific surface area of milled (mortar) Pseudevernia furfuracea was 1.8 m 2 g −1 . Pore size and its distributions are given in Fig.…”
Section: Characterization Of the Biosorbentmentioning
confidence: 99%
“…Lichens are symbiont pairings in which a fungus and green algae coexist in a mutually beneficial association; the photobiont (algae) generates carbohydrates via photosynthesis for the fungus whereas the fungus affords mineral nutrients and moisture for its symbiont. 122 It is highly significant to note also many lichens involve as the photobiont, a cyanobacterium (cyanophyta) and that in such cases, the lichen, by virtue of the strict definition of the cyanobacterium as a prokaryotic photosynthetic bacterium, represents an example of a fungal-microbe symbiosis rather than a plant-microbe example. Regardless of the precise identity of the photobiont in both classes of lichens the fungus (mycobiont) is typically the dominant partner, and thus lichens are generally classified as a form of fungal life.…”
Section: Plant-microbe Symbiosesmentioning
confidence: 99%
“…123 Biosynthetic pathways associated with production of these NPs include PKS systems (affording mono-cyclic phenols, depsides, depsidones, depsones, dibenzofurans, xanthones, naphthoquinones and anthraquinones, macrocyclic lactones, aliphatic acids, and others), the mevalonic acid pathway giving rise to steroids, carotenoids and related compounds as well as the shikimic acid pathway (giving rise to amino acid derivatives, and related shikimate-derived NPs). 125 Lichens and their assorted biosynthetic capabilities have been recently reviewed 122, 123, 125, 126 though a number of advances support the ever-increasing interest in these symbiotic systems as beacons of antimicrobial drug discovery. Particularly notable recent findings in which precise lichen structures are known and/or associated with specific antimicrobial actions are: i) work by Lou and co-workers to rigorously elucidate the structures and bioactivities of NPs from Aspergillus versicolor isolated from the lichen Lobaria quercizans leading to the identification of 14 new NPs (as exemplified by diorcinols F–H, and a number of bisabolane sesquiterpenoids such as the hydroxysydonic acid congeners shown below) as well as 15 known agents; though a focus on cytotoxic activities was reported for many of these diverse structures a number were also shown to possess antifungal activities, 127 ii) recent efforts to unveil synergistic interactions between established and clinically relevant antimicrobials such as gentamycin and levofloxacin in combination with assorted (and previously characterized) lichen-derived NP such as lobaric, α-collatolic, protolichesterinic, perlatolic and epiforellic acids from Chilean environments (inclusive of Antarctic regions) giving rise to antibacterial activities against MRSA, 125, 128 iii) studies of usnic acid, arguably the most well studied of all known lichen-derived NPs, indicating its ability to inhibit biofilm forming processes essential to the pathogenicity of Streptococccus pyrogenes , 129 iv) the revelation that the lichen endophyte-derived NP pyridoxatin displays antifungal activity against Candida albicans by interfering with ergosterol production essential to biofilm synthesis, 130 v) the recent discovery that cultured mycobionts from Sarcographa tricosa lichens (isolated from trees in Vietnam) produce eremophilane-type sesquiterpenes 3- epi -petasol, dihydropetasol and sarcographol, in addition to a number of other previously known eremophilane sesquiterpenes for which a wide assortment of antimicrobial activities have been well established, 131 vi) the revelation that norlichexanthone a well-known lichen-derived PKS product, displays antibacterial activity against S. aureus by virtue of its ability to reduce the expression of hla and RNAIII while also inhibiting DNA associations with the key regulatory protein AgrA—the result being reduced production of key virulence factors and impaired biofilm formation, 132 and vii) recent studies of the Letharia vulipina metabolite vulpinic acid that reveal this lichen-derived NP to express activity against MRSA via cell membrane and cell division targeting; these findings were in support of earlier studies by St. Clair et al showing that extracts of 36 species of lichens displayed often potent activity against four different pathogenic bacteria, of these Letharia vulipina extracts composed almost exclusively of vulpinic acid proved to be the most broadly antibacterial.…”
Section: Plant-microbe Symbiosesmentioning
confidence: 99%
“…The pharmacological potential of lichens is due to the presence of unique secondary metabolites which subsequently became excessively attractive to the pharmaceutical and cosmetic industries. As a result, a multitude of optimised processes for the quantitative extraction of these lichen metabolites has been developed [ 33 ].…”
Section: Introductionmentioning
confidence: 99%